2018
DOI: 10.1002/tox.22568
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids combined with gefitinib mediated apoptosis and autophagy of human oral cancer SAS cells in vitro and reduced tumor of SAS cell xenograft mice in vivo

Abstract: Gefitinib has been used for cancer patients and curcumin (CUR), demethoxycurcumin (DMC), or bisdemethoxycurcumin (BDMC) also shown to induce cancer cell apoptosis. However, no report shows the combination of gefitinib with, CUR, DMC, or BDMC induce cell apoptosis and autophagy in human oral cancer cells. In this study, we investigated the effects of gefitinib with or without CUR, DMC, or BDMC co-treatment on the cell viability, apoptotic cell death, autophagy, mitochondria membrane potential (MMP), and caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…In the present study, we found that DMC at 30 and 50 mg/kg significantly reduced tumor volume ( Figure 3) and tumor weight ( Figure 4C) without adverse effects on body weight of mice. This supports findings of Ni et al for the effects of another derivative of curcumin on subcutaneous xenograft tumors in human cervical HeLa cell-bearing mice in vivo (28,29). These findings are also in agreement with previous study on SAS human oral cancer cell xenografts in nude mice (29).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, we found that DMC at 30 and 50 mg/kg significantly reduced tumor volume ( Figure 3) and tumor weight ( Figure 4C) without adverse effects on body weight of mice. This supports findings of Ni et al for the effects of another derivative of curcumin on subcutaneous xenograft tumors in human cervical HeLa cell-bearing mice in vivo (28,29). These findings are also in agreement with previous study on SAS human oral cancer cell xenografts in nude mice (29).…”
Section: Discussionsupporting
confidence: 92%
“…This supports findings of Ni et al for the effects of another derivative of curcumin on subcutaneous xenograft tumors in human cervical HeLa cell-bearing mice in vivo (28,29). These findings are also in agreement with previous study on SAS human oral cancer cell xenografts in nude mice (29). A decrease of body weight is an important marker in evaluating whether or not agents induce cytotoxic effects in vivo.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the in vivo administration of gefitinib with curcumin, DMC or BDMC (30 mg/kg each, i.p., every two days) in SAS xenograft nude mice demonstrated that gefitinib co-administered with curcumin and DMC, but not with BDMC, induced a significant reduction in tumor growth in mice, compared to single treatments. Tumor tissue analysis showed the increased expression of caspase-6 and -7, associated with apoptosis, and of Beclin 1 and LC3, associated with autophagy, by the combination of gefitinib with curcuminoids [230]. The autophagic activation induced by the combined treatment of curcumin and gefitinib was also evaluated in gefitinib-resistant NSCLC cells H157 and H1299.…”
Section: Curcuminoidsmentioning
confidence: 99%
“…Accumulated evidence suggests that autophagy plays an important role in cell apoptosis mediated by anti-cancer drugs [9,10]. Furthermore, the p53/damage-regulated autophagy modulator (DRAM) signaling pathway has been reported to be involved in regulating autophagy [11,12].…”
Section: Introductionmentioning
confidence: 99%